Eco-printing Leather Quality in Different Mordant Methods - Pancapalaga, Wehandaka; Hartati, Endan Sri; Hidayati, Asmah (Universitas Halu Oleo, 2022)
The leather coloring technique using the eco-printing method is carried out by transferring the colors and motifs of plants on the leather media by direct contact. This process requires mordant to maximize the color. The use of mordant is done in 3 ways, namely mordant is done at the beginning (pre-mordanting), mordant is done simultaneously (meta-mordanting), and mordant is done at the end (post-mordanting). This study aims to determine the quality of eco-printing leather with the implementation of different mordant methods. The research materials were 16 pieces of sheep’s crust leather. The research treatment was using various mordant methods, namely pre-mordanting, meta-mordanting, and post-mordanting. Colorfastness, tensile strength, elongation, tear strength, flexibility, and fracture resistance were among the eco-printing leather qualities evaluated. The research was carried out in an experimental setting using a completely randomized design. To conclude, the best mordant method was carried out at the beginning of the eco-printing process on leather media (pre-mordanting), where the quality of eco-printing leather obtained of 5.44±0.968 mm, crack resistance (distance) of 8,78±0.97 mm, the tensile strength of 1743.64 ±45.26 N/cm2, leather elongation of 55.15±10.26 %, tear strength of 268.24±132.49 N/cm, sewing strength of 1247.12± 649.91 N/cm, colorfastness of wet rubbing rated 4 (good), and dry rub of 4 (good).Keywords: quality, eco-printing leather, crust leather, mordant technique, tanned leather